(untitled) (European Journal of Interdisciplinary Research and Development, 2023)
Currently, the number of children with aggressive behavior is increasing. This is caused by many factors, including the deterioration of the social living conditions of children, the increase in pathological births, damage to the child’s brain, and the promotion of violence by the mass media. Aggression is often found in mental illnesses. His therapy is primarily the medicine prescribed by the doctor. But in this case, psycho-corrective methods play an important role, because without them it is impossible for the child to adapt to the environment. Many studies have shown that aggressive children leave families with aggressive relationships. Therefore, the role of family therapy - a method of restoring the functional unity of the family by normalizing the relationships and mental health of family members - is very important. An important step in the work to correct aggressive behavior is to do personal work. In carrying out this type of work, the psychologist will study in detail the reasons for the child’s aggressive characteristics, help him to overcome individual problems in emotional stability and personal spheres, help to determine what role the child can play in the group. The child, in turn, in this case can get acquainted with the rules and norms of correctional work, give impetus to internal changes, respond to aggressive manifestations under favorable conditions. The reasons for aggression in children may also depend on their health. Some body diseases or brain diseases, negativity of relations in the family affect the child. There are many classifications of aggression, but usually one person shows several types of aggression at the same time, they constantly change and overlap.